Consumptive Behaviour of Gen-Z and Identity in the Digital Era - Rahma Hayati Harahap; Nahwa Zainab Marpaung; Rowiyah Asengbaramae (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2023)
The era of digital natives has offered many conveniences, including social media and e-commerce. This use contributes to personal branding, resulting in the creation of self-identity. This study aims to describe the social reality of Gen-Z in performing consumptive behavior for personal identity in the Digital Natives Era with the AGIL concept. This research uses descriptive qualitative methods. Data collection techniques used are interviews and observations. There were five informants in Medan. The results showed that Gen-Z's consumptive behavior in Online Shopping in the Digital Natives Era was influenced by the demands of forming personal branding through fashion, which was becoming a trend on social media. Some informants normalize their consumptive behavior to follow directions and develop personal branding. According to the theory of Parsons (AGIL), this phenomenon results from social change related to consumption behavior. This study concludes that the need to form personal branding has manipulated students' awareness of wasteful behavior.